2014
DOI: 10.1104/pp.114.240929
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Development of the Root Cap in Rice

Abstract: (J.X.).The tip of the root is covered by a thimble-shaped root cap that is the site of perception and transduction for many environmental stimuli. Until now, little was known about how the root cap of rice (Oryza sativa) develops and functions to regulate the adaptive behavior of the root. To address this, we examined the formation of the rice root cap during embryogenesis and characterized the anatomy and structure of the rice radicle root cap. We further investigated the role of the quiescent center in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 50 publications
1
25
0
2
Order By: Relevance
“…These experiments reveal that Glu also triggers a Ca 2+ response in the monocotyledonous plant rice and point to the conservation of an amino acid responsive Ca 2+ signaling system in this species. This is in agreement with the presence of a complex family of GLRs in rice and with their reported function (Li et al ., ; Wang et al ., ). However, considering both experiments, the hyperpolarization and Glu response analyses, our study also reveals fundamental differences in Ca 2+ signaling between the model species Arabidopsis and rice.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These experiments reveal that Glu also triggers a Ca 2+ response in the monocotyledonous plant rice and point to the conservation of an amino acid responsive Ca 2+ signaling system in this species. This is in agreement with the presence of a complex family of GLRs in rice and with their reported function (Li et al ., ; Wang et al ., ). However, considering both experiments, the hyperpolarization and Glu response analyses, our study also reveals fundamental differences in Ca 2+ signaling between the model species Arabidopsis and rice.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, recent studies revealed, for example, the conservation of complete Ca 2+ -activated modules for the regulation of potassium (K + ) uptake between Arabidopsis and rice (Xu et al, 2006;Li et al, 2014). Also, channels that are involved in the formation of Ca 2+ signals such as glutamate (Glu) receptor-like (GLR) proteins have been reported to fulfill crucial functions during rice development and environmental responses Wang et al, 2014). By contrast, despite several early reports about the role of Ca 2+ and calmodulin in rice stress responses, which were largely based on the application of inhibitors or agonists for Ca 2+ signaling, no high-resolution data on Ca 2+ signatures in rice have been reported to date (Aurisano et al, 1995;Yemelyanov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1b) [9,30], while the lateral root cap initial cell and the epidermal initial cell were separate in rice (Fig. 1a) [29]. Therefore, the lateral root cap in Arabidopsis seems to be a derivative of L1 structure.…”
Section: Cell Lineage In the Body Layer Specialization Of Rice And Armentioning
confidence: 95%
“…1a). The rice root cap, which was initiated from the columella initial cell and lateral root cap initial cell [29], was independent from the three layers ( Fig. 1a).…”
Section: Cell Lineage In the Body Layer Specialization Of Rice And Armentioning
confidence: 99%
“…Kumpf et al (2014) investigated how coordination of cell division between daughters of root meristem initials and their shift into endo-reduplication and elongation is important for correct root meristem function. Wang et al (2014) studied the establishment and regeneration of the rice root cap.…”
mentioning
confidence: 99%